Analisis Kandungan Logam Berat pada Minyak Ikan Sardine (Sardinella sp.) Hasil Penepungan dari Bali - Haryati, Kristina (Cenderawasih University, 2024)
Sardines, or lemuru, are a group of pelagic fish that are often found in the waters of the Bali Strait because they have potential economic and strategic valuesuch as a source of income for fishermen, a provider of raw materials for theprocessing industry, and a source of local income. Sardine, or lemuru fish, is apelagic fish that has a high oil content and can be used in the processing industry.In processing industries such as the flour industry, waste will be produced, one ofwhich is liquid waste such as fish oil. Fish oil, which is a by-product, can be utilizedfurther, but the impurity components, one of which is the heavy metal content in theoil, must be removed first. The way to remove or reduce the concentration of heavymetals in fish oil is through a series of purification techniques. The aim of this studywas to determine the heavy metal content in sardine or lemuru fish oil from Bali,which has been purified first, and then compare the results of these heavy metaltests with the results of other studies. The purification carried out was divided into3 stages, namely degumming using water (without citric acid), neutralization usingNaOH, and bleaching using magnesol XL 5% (w/v). Crude fish oil (unrefined) andpure fish oil are then tested for heavy metals. The results show that purifying fishoil can reduce heavy metal content. These results are also in line with researchconducted by several previous researchers. So it can be concluded that the refiningstage can reduce the heavy metal content so that it meets the International Fish OilStandard (IFOS).